Rios não recomendados: atendimento socioeducativo de meninas trans e travestis em cumprimento de medidas privativas de liberdade no Maranhão - DUTRA, Livia Almeida (2023)
The research entitled “RIVERS NOT RECOMMENDED: socio-educational care for trans girls and transvestite in compliance with custodial measures in Maranhão”, aims to analyze the socio-educational care carried out at the Centro Socioeducativo Florescer in Maranhão with trans girls and transvestite in compliance of deprivation of liberty, without losing sight of the fact that they are inserted in a cisheteronormative and heterosexual society, permeated by various social markers, such as class, race and gender. The research, of a qualitative nature, was methodologically guided by Dialectical Historical Materialism, in an effort of critical interpretation in the perspective of the totality of the social reality of trans and transvestite adolescents in compliance with custodial measures. The analysis of the care given to adolescents trans and transvestites in compliance with the private socio-educational measures in question, based on theoretical reflections articulated with the regulations and the participants speeches, collected in the empirical research, through techniques such as systematic observation and interviews semi-structured with professionals from the Centro Socioeducativo Florescer team, and a trans teenager who was serving a custodial measure from November 2022 to February 2023. Its results point out (or reaffirm) challenges and difficulties that permeate the lives of those who perceive themselves to be outside socially constructed standards – whiteness, bourgeoisie, cisgender and heterosexuality. Urgencies persist for the effectiveness of social protection for the trans and transvestite population in concrete reality. In this sense, it becomes imperative that the State pays more attention to public policies that protect and ensure trans experiences, whether or not they are complying with socio-educational measures, investments in continued training in the bodies that make up the Socio-Educational System, with reflections on gender and sexualities, in order to overcome/restrain violations as a result of heteronormative impositions and legal restrictions.